Insde Japan's financial market - Viner, Aron (The Japan times, 1987)
The paper gives an overview of the current state of markets for money, bonds, equities and derivatives arguing that for reform to become successful measures to develop an entirely different market culture were needed. It calls for a redefinition of the role of interest groups in the financial intermediation process – including the role of government.